Developing the information management capacity of the Caribbean Community Secretariat ([S.l.] [s.n.])
Identifies the technologies and skills which must be acquired and policies and projects implemented to enable the Secretariat to successfully and effectively carry out its mandate during the period 2001-2004.
Keywords: INFORMATION MANAGEMENT